2014
DOI: 10.1002/dmrr.2486
|View full text |Cite
|
Sign up to set email alerts
|

Steroid‐induced diabetes: a clinical and molecular approach to understanding and treatment

Abstract: Summary Since the advent of glucocorticoid therapy for autoimmune disease in the 1940s, their widespread application has led to the concurrent therapy-limiting discovery of many adverse metabolic side effects. Unanticipated hyperglycemia associated with the initiation of glucocorticoids often leads to preventable hospital admissions, prolonged hospital stays, increased risks for infection and reduced graft function in solid organ transplant recipients. Challenges in managing steroid-induced diabetes stem from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
204
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(216 citation statements)
references
References 36 publications
4
204
0
8
Order By: Relevance
“…Many studies worldwide like Kim SY et al of Korea done in 2011 and Hwang JL et al of USA done in 2014 showed that patients with respiratory problems like chronic obstructive lung diseases on steroids the glucose metabolism mainly affected by the dose and total duration of steroids but there is no agreement between this study and other studies regarding the effect of steroid dose and duration on glucose metabolism. 16,36,37 This inconsistency can be explained by small sample size as compared with other studies.…”
Section: Discussionmentioning
confidence: 90%
“…Many studies worldwide like Kim SY et al of Korea done in 2011 and Hwang JL et al of USA done in 2014 showed that patients with respiratory problems like chronic obstructive lung diseases on steroids the glucose metabolism mainly affected by the dose and total duration of steroids but there is no agreement between this study and other studies regarding the effect of steroid dose and duration on glucose metabolism. 16,36,37 This inconsistency can be explained by small sample size as compared with other studies.…”
Section: Discussionmentioning
confidence: 90%
“…The mechanism of hyperglycemia is predominantly decreased insulin sensitivity in target tissues leading to insulin resistance. In the liver it results in increased basal glucose production, and in the periphery, especially the adipose and skeletal tissues, glucose use is impaired (18). Glucocorticoids decrease insulin-mediated glucose uptake by inhibiting glucose transporter type 4.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids decrease insulin-mediated glucose uptake by inhibiting glucose transporter type 4. Additionally they increase fatty acid release into the blood from the liver which further interferes with glucose utilization, especially by skeletal muscles (18)(19)(20). They can also cause beta cell dysfunction in the pancreas leading to an inability to release insulin.…”
Section: Discussionmentioning
confidence: 99%
“…7 Corticosteroid induced DM by increasing blood glucose level to abnormal numbers in patients with or without previous history of DM. 19 Corticosteroids cause hyperglycemia by stimulating proteolysis, increasing enzymes that stimulate gluconeogenesis, and inhibiting glucose intake in muscle and fat tissues. Synthetic corticosteroids like prednisone and dexamethasone are more potent to decrease carbohydrate tolerance compared to natural corticosteroids like hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%